Leadership in Higher Education: An Examination of Styles, Assertiveness, and Creative Problem-Solving - Mary Grace Gumpal; Joseph Mirvin Dadap (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2024)
This research investigates the complexities of leadership within the higher education sector, focusing on leadership styles, assertiveness levels, and creativity in problem-solving among university leaders. The primary objective of this study is to provide a comprehensive analysis of the experiences and behaviors of these leaders, shedding light on their effectiveness in managing the complexities inherent in educational institutions. The study employs a mixed-method research design, utilizing the Consensual Qualitative Research-Modified (CQR-M) approach to offer a nuanced understanding of the experiences and behaviors of top-ranking officials. The participating institutions, Isabela State University and Dela Salle Dasmarinas in Cavite City, provide a diverse context for the exploration of leadership dynamics. The quantitative findings reveal that a substantial 83.3% of the participants exhibit a free-rein leadership style, signifying a preference for autonomy in decision-making. Additionally, a majority of the university leaders emerge as non-assertive and intellectual conformists, shedding light on prevalent communication patterns and cognitive approaches within the leadership cadre. Qualitative analysis yields five major themes that encapsulate both the characteristics and challenges faced by university leaders. These themes provide a comprehensive narrative, addressing the nuances of their experiences and shedding light on the multifaceted nature of leadership within complex educational institutions. This study contributes to the existing body of knowledge by not only quantifying prevalent leadership styles and traits but also by providing a rich qualitative exploration of the contextual factors influencing university leadership. The insights garnered from this research hold significance for academic institutions aiming to enhance leadership effectiveness, offering practical implications for leadership development programs and fostering a deeper understanding of the complexities faced by educational leaders in managing the evolving landscape of higher education.